Pleomorphic adenoma mimicking oral lipoma - Janaina Santos; Rani Gonçalo; José Santos; Marcelo Silveira; Lélia Queiroz (Editorial Ciencias Médicas, 2020)
Introduction: Pleomorphic adenoma is the most common benign salivary gland neoplasm. It may affect major and minor salivary glands. It presents at a broad age range and is characterized by great clinical and pathological variability and high recurrence rates. Objective: Describe a case of pleomorphic adenoma, with emphasis on clinical and pathological aspects, differential diagnosis and clinical management. Case report: A male 72-year-old patient presents with a well-defined nodular lesion in the lower section of the left maxillary groove with a time of evolution of four years. Excisional biopsy was performed. The diagnostic hypotheses considered were lymphoid hyperplasia, pleomorphic adenoma and lipoma, with greater attention to the latter, due to the fact that it floated in formaldehyde. Microscopic examination revealed proliferation of epithelial and myoepithelial cells amidst a variable stroma. Thus, a histopathological diagnosis of pleomorphic adenoma was issued. Conclusion: The present study highlights the importance of careful histopathological examination to rule out other diagnostic hypotheses and malignant neoplasms. Next, clinical and microscopic findings will lead to an accurate diagnosis indispensable to adopt an appropriate therapeutic approach.